Interleukin-10/Interleukin-5 responses at birth predict risk for respiratory infections in children with atopic family history - Zhang, Guicheng; Rowe, J.; Kusel, M.; Bosco, A.; McKenna, K.; De Klerk, N.; Sly, P.; Holt, P. (American Thoracic Society, 2009)
Rationale: Respiratory infections in early life are associated with risk for wheezing bronchiolitis, especially in children at high risk of atopy. The underlying mechanisms are unknown, but are suspected to involve imbalance(s) in host defense responses against pathogens stemming from functional immaturity of the immune system in this age group. Objectives: To assess the contribution of eosinophil-trophic IL-5, and the potent antiinflammatory cytokine IL-10, to risk for infection in early life. Measurements and Main Results: We prospectively monitored a cohort of 198 high-risk children to age 5 years, recording every acute respiratory infection episode and classifying them by severity. We measured cord blood T-cell capacity to produce IL-10 and IL-5, and related these functions to subsequent infection history. IL-10 and IL-5 were associated, respectively, with resistance versus susceptibility to infections. The greatest contrasting effects of these two cytokines were seen when they were considered in combination by generating IL-10/IL-5 response ratios for each subject. The low IL-10/high IL-5 T-cell response phenotype was strongly associated with susceptibility to all grades of acute respiratory infection, relative to the more resistant high IL-10/low IL-5 phenotype. Conclusions: Excessive production of IL-5 by T cells at birth is associated with heightened risk for subsequent severe respiratory infections, and this risk is attenuated by concomitant IL-10 production. The underlying mechanisms may involve IL-10-mediated feedback inhibition of IL-5-dependent eosinophil-induced inflammation, which is a common feature of host antiviral responses in early life.